Narrowband Spectrum Sensing in Cognitive Radio: Detection Methodologies - Jain, Praneeth P; Pawar, Pradeep R; Patil, Prajwal; Pradhan, Devasis (International Journal of Computer Sciences and Engineering, 2019)
With the rapid development in the technology, and every device connected to the internet and increase in wireless sensing devices, the spectrum is becoming more and more congested. To solve the spectrum scarcity problem, Cognitive Radio technology is used. The details about the function of cognitive radio such as spectrum sensing, spectrum management, spectrum decision and spectrum handoff are illustrated in this paper. Cognitive radio senses the spectrum for the presence of idle spectrum and allocates the unused frequency band to the cognitive user. When the secondary user is transmitting the data, the cognitive radio senses for the unused spectrum. If the primary user wants to access the channel, then the cognitive radio allocates the secondary user in the nearby unused frequency band. In this paper we are mainly focusing on narrow band spectrum sensing. Under narrow band spectrum sensing various detection techniques such as Energy detection, Matched filter, Covariance detector, Waveform detector and Cyclo-stationary detection are discussed in detail below. The efficiency of the spectrum sensing can be increased with the cooperative spectrum sensing in which multiple secondary users cooperate in sensing the spectrum.